PENGARUH KEPEMIMPINAN DAN KOMUNIKASI TERHADAP KEPUASAN KERJA MELALUI MOTIVASI PEGAWAI DI KECAMATAN PANGGUNGREJO KOTA PASURUAN - Yoyok; Woro Utari; Muninghar (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2024)
The purpose of this study was to determine the description of leadership, communication, motivation and job satisfaction of employees in Panggungrejo District, Pasuruan City, and to determine and examine the direct and indirect effects of leadership and communication on job satisfaction through employee motivation in Panggungrejo District, Pasuruan City. This type of research is explanatory research, the approach in this research is quantitative, the population of this research is all employees of Panggungrejo District, Pasuruan City, totaling 46 people. The sample is 44 people with total sampling technique. In this study, data analysis used SEM and PLS software. Based on the results of the analysis it can be concluded that leadership, communication, motivation and job satisfaction of employees in Panggungrejo District, Pasuruan City are in the high category. Leadership has a significant positive influence on employee motivation. Communication has a significant positive effect on employee motivation. Leadership has an insignificant positive effect on employee job satisfaction. Communication has a positive but not significant effect on employee job satisfaction. Work motivation has a significant positive effect on employee job satisfaction. Leadership has a significant positive effect on employee job satisfaction. Communication has a significant positive effect on employee job satisfaction.